The oncogenic role and prognostic value of PXDN in human stomach adenocarcinoma - Yuan Tian; Shenghui Qiu; Song Yang; Yuanjian Jiang; Hao Hu; Chengcheng Yang; Jinyong Cao; Shaomin Chen; Mingqing Hao; Hongling Li; Jianlin Zhu (BMC Cancer)
Abstract Stomach adenocarcinoma (STAD) is known for its high prevalence and poor prognosis, which underscores the need for novel therapeutic targets. Peroxidasin (PXDN), an enzyme with peroxidase activity, has been linked to cancer development in previous studies. However, its specific role in STAD is not well understood. In our study, we used public databases and clinical specimens to determine that PXDN expression is significantly elevated in STAD tissues and serves as an independent prognostic marker for patient outcomes. Our in vitro assays demonstrated that silencing PXDN significantly reduced STAD cell proliferation, invasion, and migration. Mechanistically, we found that PXDN promotes epithelial‒mesenchymal transition and angiogenesis in STAD cells and may be regulated by the PI3K/AKT pathway. Further analysis revealed that PXDN levels affect the sensitivity of STAD cells to various chemotherapeutic and small molecule drugs. Additionally, we observed a significant association between PXDN levels and the abundances of various immune cell types in patients with STAD. Our study highlighted a strong link between PXDN levels and the tumor immune microenvironment (TIM), suggesting that PXDN is a useful metric for evaluating the response to immune checkpoint inhibitors. Moreover, we found that PXDN is significantly associated with multiple immune checkpoints. In summary, our findings indicate that PXDN plays a critical role in STAD and that its level could serve as a potential prognostic biomarker. Thus, targeting PXDN may represent an effective treatment strategy for STAD.